Approach combining on-line metal exchange and tangential-flow ultrafiltration for in-situ characterization of metal species in humic hydrocolloids - Goveia, Danielle [UNESP]; Lobo, Fabiana Aparecida [UNESP]; Burba, Peter; Fraceto, Leonardo Fernandes [UNESP]; Dias Filho, Newton Luiz [UNESP]; Rosa, Andre Henrique [UNESP] (Springer Heidelberg, 2010)
This paper deals with the development and optimization of an analytical procedure using ultrafiltration and a flow-injection system, and its application in in-situ experiments to characterize the lability and availability of metal species in humic-rich hydrocolloids. The on-line system consists of a tangential flow ultrafiltration device equipped with a 3-kDa filtration membrane. The concentration of free ions in the filtrate was determined by atomic-absorption spectrometry, assuming that metals not complexed by aquatic humic substances (AHS) were separated from the complexed species (M-AHS) retained by the membrane. For optimization, exchange experiments using Cu(II) solutions and AHS solutions doped with the metal ions Ni(II), Mn(II), Fe(III), Cd (II), and Zn(II) were carried out to characterize the stability of the metal-AHS complexes. The new procedure was then applied in-situ at a tributary of the Ribeira do Iguape river (Iguape, São Paulo State, Brazil) and evaluated using the ions Fe(III) and Mn(II), which are considered to be essential constituents of aquatic systems. From the exchange between metal-natural organic matter (M-NOM) and the Cu(II) ions it was concluded that Cu(II) concentrations > 485 mu g L(-1) were necessary to obtain maximum exchange of the complexes Mn-NOM and Fe-NOM, corresponding to 100% Mn and 8% Fe. Moreover, the new analytical procedure is simple and opens up new perspectives for understanding the complexation, transport, stability, and lability of metal species in humic-rich aquatic environments.
Keywords: Lability/availability; Metal; Aquatic humic substances; Ultrafiltration